Persepsi Kemudahan, Kegunaan, Keamanan, dan Kerahasiaan terhadap Minat Wajib Pajak Orang Pribadi dalam Menggunakan E-Filing dengan Kesiapan Teknologi Informasi Sebagai Variabel Moderating pada KPP Pratama Serang Barat - Gemilang, Sandra; Lestari, Dini Martinda; Afriani, Raden Irna (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
The purpose of this research is to analyze the effect of perceived ease of use, usefulness, security, and confidentiality on the interest of individual taxpayers in using E-Filing, with information technology readiness as a moderating variable. Many individual taxpayers still face challenges in using E-Filing, such as technology access, understanding of use, and lack of socialization and education about the benefits of E-Filing. This research uses an associative and descriptive quantitative method with 100 taxpayer respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method using SmartPLS 3.2.9 software. The results of hypothesis testing indicate that perceived ease of use and usefulness have a significant effect on taxpayers' interest in using E-Filing. However, perceptions of security and confidentiality do not have a significant effect. Moreover, perceptions of ease of use, usefulness, security, and confidentiality do not have a significant effect on information technology readiness. In conclusion, perceptions of ease of use and usefulness affect taxpayers' interest in using E-Filing, while security and confidentiality do not have an effect. Information technology readiness does not moderate the effect of perceptions of ease of use, usefulness, security, and confidentiality on taxpayers' interest in using E-Filing.